2018
DOI: 10.1002/chem.201705090
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights on Human Phosphoglucomutase Revealed by Transition Path Sampling and Molecular Dynamics Calculations

Abstract: Human α-phosphoglucomutase 1 (α-PGM) catalyzes the isomerization of glucose-1-phosphate into glucose-6-phosphate (G6P) through two sequential phosphoryl transfer steps with a glucose-1,6-bisphosphate (G16P) intermediate. Given that the release of G6P in the gluconeogenesis raises the glucose output levels, α-PGM represents a tempting pharmacological target for type 2 diabetes. Here, we provide the first theoretical study of the catalytic mechanism of human α-PGM. We performed transition-path sampling simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…An analysis of the C α root mean square fluctuations (RMSF), relative to the energy-minimized starting structures, shows that the D4 loop (residues 505–511) is the most highly mobile region of the protein, even in the R503Q variant (Figures 4 and S4C–D). (A previous study of PGM1 mechanism by MD showed a similar result for WT enzyme (Bras et al, 2018)). We further examined the range of conformers of the D4 loop sampled during the MD simulation, and find that the conformers observed in the crystal structures of the missense variants and PGM1-G6P complex are encompassed within this range (Figure 4B).…”
Section: Resultssupporting
confidence: 72%
“…An analysis of the C α root mean square fluctuations (RMSF), relative to the energy-minimized starting structures, shows that the D4 loop (residues 505–511) is the most highly mobile region of the protein, even in the R503Q variant (Figures 4 and S4C–D). (A previous study of PGM1 mechanism by MD showed a similar result for WT enzyme (Bras et al, 2018)). We further examined the range of conformers of the D4 loop sampled during the MD simulation, and find that the conformers observed in the crystal structures of the missense variants and PGM1-G6P complex are encompassed within this range (Figure 4B).…”
Section: Resultssupporting
confidence: 72%
“…Both binding orientations must occur during the catalytic cycle depending on whether the first or second phosphoryl transfer needs to or has already taken place, although only the first has been observed in crystal structures in the superfamily 16 . Other catalytically relevant states involving E deP :I, which are not characterizable by crystallography, include the two phosphoryl transfer steps, shown for a related enzyme to proceed through a concerted S N –2-like mechanism, with a loose, metaphosphate-like transition state 17 . Another is the dynamically reorienting G16P present in between phosphoryl transfer steps [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GP catalyzes the rate-limiting step of glycogen breakdown, releasing glucose-1-phosphate. After this, phosphoglucomutase shifts the position of the phosphate in the sugar, making it suitable to fulfill the energetic requirements of the organism [ 155 ]. GP is an allosteric enzyme that changes between active (GPa) and tense (GPb) conformation states.…”
Section: Why Anthocyanins?mentioning
confidence: 99%